Experimental Study on Seismic Behavior of Concrete-Filled L-Shaped Steel Tube Columns. Issue 7 (July 2013) - Shen, Zu-Yan; Lei, Min; Li, Yuan-Qi; Lin, Zhen-Yu; Luo, Jin-Hui
Concrete-filled L-shaped steel tube columns can be used to save architectural space at room corners, and may have many advantages of structural behavior of common concrete-filled steel tubes as columns. In this paper, the seismic behavior of concrete-filled L-shaped steel tube columns (CFLSTs) was investigated. Six specimens subjected to a constant axial load and cyclically varying lateral loading were tested to study the effects of width to depth ratio of section, depth to thickness ratio of steel tube and axial load level on the strength, as well as stiffness, ductility and energy dissipation of CFLST columns. Experimental results showed that the displacement ductility of CFLST columns decreased significantly with the increase of axial load level, and the strength and stiffness degradations of CFLST columns were more significant with higher axial load level. With the increase of depth-thickness ratio of steel tube and depth-width ratio of section, the ductility and the lateral ultimate load-carrying capacity of CFLST columns also decreased gradually. All CFLST columns exhibited favorable energy dissipation and ductility, even for the columns subjected to high axial load, which indicates that this type of composite columns is adoptable in practical engineering, especially in seismic regions.